2019
DOI: 10.1097/01.aoa.0000575248.76563.52
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Fetal Heart Rate Characteristics Associated With Neonatal Encephalopathy: A Case-Control Study

Abstract: (BJOG. 2018;125(11):1480–1487) Neonatal encephalopathy (NE) is characterized by abnormal neurological function that presents with decreased level of consciousness or seizures, difficulty maintaining respirations, and abnormal reflexes or tone. This clinical condition is identified shortly after birth with an incidence of 2 to 6/1000 live births. There is incomplete understanding of the etiology of NE and no evidence-based interventions to prevent its occurrence. The objective of the study was to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…Most previous FHR studies have focused on a predefined period before delivery. Frey et al reported that ACOG category II traces in the last half hour before delivery are common and do not help to identify NE [18]. In our study, at least one suspicious or pathological segment was found in ½ and ¼ of controls, respectively.…”
Section: Discussioncontrasting
confidence: 61%
“…Most previous FHR studies have focused on a predefined period before delivery. Frey et al reported that ACOG category II traces in the last half hour before delivery are common and do not help to identify NE [18]. In our study, at least one suspicious or pathological segment was found in ½ and ¼ of controls, respectively.…”
Section: Discussioncontrasting
confidence: 61%
“…Since the beating of the fetal heart is periodic, the frequency shift signal also has a certain periodicity. By processing the frequency shift signal, the fetal heart rate can be calculated, which is the basic principle of extracting the fetal heart rate using ultrasonic Doppler technology [11].…”
Section: Methodsmentioning
confidence: 99%
“…[59][60][61][62][63][64] If these episodes of hypoxaemia continue, fetal cardiac output is progressively compromised, leading to fetal hypotension and hypoperfusion, potentially resulting in hypoxic-ischemic brain injury. [65][66][67][68][69][70][71] The progressive worsening intrapartum fetal hypoxaemia can be observed as changes in baseline FHR and deeper FHR decelerations, 6,72,73 but once deeper decelerations are established there is typically little further change in FHR. 74 Increased FHRV typically develops in the early stage of fetal hypoxia 23,29,36,43 but can be seen also in FHR tracings of fetuses during the preterminal stage of repeated asphyxia (Appendix S1).…”
Section: Feta L a Da P Tat Ion Du R I Ng L A Bou Rmentioning
confidence: 99%